Inovasi Pelayanan Pertanahan Berbasis Inklusi dan Kearifan Lokal Melalui Layanan Spesial Tanpa Antri dan Pojok Angkringan Konsultasi - Kusumo Wijoyo, Danang; Pujiriyani, Dwi Wulan; Farid, Abdul Haris (Tunas Agraria, 2023)
Since 2018, the Bantul Land Office has been actively working on reforms to raise the caliber of public services, one of which is the use of various public service innovations. The Bantul Land Office then took the initiative to create several land service innovations without using a technology base, namely LASTRI (Special Service without Queuing) and PANGKON (Consulting Corner) innovations as breakthroughs in convenience and fluency at service counters, including for those with special needs. This study will describe public service activities at the service counter of the Bantul Land Office, reviewing the application of LASTRI and PANGKON innovations, including the benefits and advantages offered both in terms of service providers and recipients, as well as the influence given to improving the quality of public services at the Bantul Land Office, using qualitative research methods with a descriptive approach. For the Bantul Land Office itself, the benefits obtained from the LASTRI and PANGKON innovations are that they can improve the quality of land services to the community and obtain community satisfaction through the Community Satisfaction Index (IKM) survey, as well as being more open and closer to the community. These innovations are also one of the indicators of achievement as a series of declarations for the development of the Integrity Zone, where the Bantul Land Office later received the title of Corruption Free Area (WBK) by the Ministry of Administrative and Bureaucratic Reform in December 2020.   Pembaruan demi pembaruan dalam rangka peningkatan kualitas pelayanan publik gencar dilakukan oleh Kantor Pertanahan Kabupaten Bantul sejak tahun 2018 lalu, salah satunya melalui pemanfaatan berbagai inovasi pelayanan publik. Kantor Pertanahan Kabupaten Bantul kemudian berinisiatif menciptakan beberapa inovasi pelayanan pertanahan tanpa menggunakan basis teknologi, yakni inovasi LASTRI (Layanan Spesial Tanpa Antri) dan PANGKON (Pojok Angkringan Konsultasi) sebagai terobosan kemudahan dan kelancaran di loket pelayanan, termasuk bagi mereka yang berkebutuhan khusus. Penelitian ini bertujuan untuk menganalisis penerapan inovasi LASTRI dan PANGKON serta pengaruh yang diberikan pada peningkatan kualitas pelayanan publik di Kantor Pertanahan. Penelitian dilakukan dengan menggunakan metode kualitatif. Hasil penelitian menunjukkan bahwa Inovasi LASTRI dan PANGKON dapat meningkatkan kualitas pelayanan pertanahan. Inovasi diterima oleh masyarakat yang ditunjukkan dari kepuasan masyarakat terhadap pelayanan yang diberikan kantor pertanahan. Pelayanan menjadi lebih terbuka dan dekat dengan masyarakat. Inovasi-inovasi ini juga merupakan salah satu indikator capaian prestasi sebagai rangkaian deklarasi pembangunan Zona Integritas dimana Kantor Pertanahan kemudian memperoleh predikat Wilayah Bebas dari Korupsi (WBK) oleh kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi pada Desember 2020.